Preliminary in vitro investigation of Litsea petiolata extracts for sustainable control of bacterial leaf blight in rice caused by Xanthomonas oryzae pv. oryzae - Rattanaanan, Jantaravipa; Soiklom, Siriwan; Chuaysrinule, Chananya; Maneeboon, Thanapoom (Health Science, Science and Technology Reviews, 2025)
Litsea petiolata, locally called Tham Mung, is widely distributed across tropical and subtropical regions of Asia, and North and South America. This plant is notable for its ecological significance and cultural relevance. Renowned for its rich secondary metabolites, especially phenolic compounds, L. petiolata has been studied for its medicinal and antimicrobial properties. This study investigates the phenolic content and antibacterial activity of ethanol and hexane extracts from the leaves and stems of L. petiolata, specifically targeting Xanthomonas oryzae pv. oryzae (Xoo), the bacterium responsible for bacterial leaf blight in rice. High-performance liquid chromatography identified key phenolic compounds, including vanillic acid in the leaves and 4-hydroxybenzoic acid in the stems. The antibacterial efficacy of these extracts was evaluated using clear zone assays, minimum inhibitory concentration, and minimum bactericidal concentration testing. The results indicated that the ethanol extract from the leaves exhibited the most potent antibacterial activity, significantly inhibiting the growth of Xoo. These findings suggest that L. petiolata holds considerable potential as a source of natural antibacterial agents, offering an environmentally sustainable alternative to chemical treatments for managing bacterial diseases of rice.